Electrical systems and mechatronics - Hilgers, Michael; Achenbach, Wilfried 1955- (Berlin, Germany Springer, 2021)
The aim of this work, consisting of 9 individual, self-contained booklets, is to describe commercial vehicle technology in a way that is clear, concise and illustrative. Compact and easy to understand, it provides an overview of the technology that goes into modern commercial vehicles. Starting from the customer's fundamental requirements, the characteristics and systems that define the design of the vehicles are presented knowledgeably in a series of articles, each of which can be read and studied on their own. This volume, Electrical Systems and Mechatronics, offers an introduction to the mechatronics in a commercial vehicle. The electrical and electronic systems are presented, up to and including the advanced driver assistance systems. The compressed air system and the commercial vehicle brake are explained to give the reader a comprehensive overview, such as is helpful for understanding in training and in practice. Content Electrical systems and mechatronics.- Compressed air system.- Brake system.- Advanced driver assistance systems.- Telematic systems.- Abbreviations and symbols. The target groups Participants in master classes and those studying individual aspects of commercial vehicle technology Professors and lecturers instructing in the field of commercial vehicle technology Consultants and experts who need background knowledge and technical expertise regarding commercial vehicle technology Personnel working in the commercial vehicle technology or supply industry who are assigned to a new work area Cost planners and logistics companies The Authors Dr. Michael Hilgers is currently director of the testing center at BFDA, a Foton Daimler truck joint venture in China. Before that he was head of different development departments in Commercial Vehicle Development at Mercedes-Benz Trucks. Dr. Wilfried Achenbach has worked in the automotive industry for over 30 years. Recently he retired as Head of Development at Daimler Trucks North America.
Electronic reproduction
Keywords: Trucks -- Electric equipment